2011
DOI: 10.5897/ajb11.535
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding frequency on growth performance and body composition in juvenile rainbow trout (Oncorhynchus mykiss) reared in cold seawater

Abstract: This study was done to investigate the effects of different feeding frequencies on the growth, feed efficiency and specific growth rate (%) of juvenile of rainbow trout (Oncorhynchus mykiss, weight 16.44±0.22 g) rearing in cold sea water conditions (5.8 to 9.3°C; 17 to 18 ppt). Fish were fed on a commercial feed to the apparent satiation twice a day (Control), six times every day (TD6), four times every day (TD4) and three times every day (TD3) for 8 weeks of the trial. The fish fed to satiation in all the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…The higher protein content of the experimental fish means that, they converted and utilized the protein from the feed into their body prtein. This result is similar with that of Marimuthu et al (2010) and Ali and Onder (2011). The findings were consistent with those of (Nubia et al, 2014) who found that, the protein content of wild catfish was 19.33±0.25%.…”
Section: Effect Of Experimental Diets On Initial and Final Muscles Co...supporting
confidence: 93%
“…The higher protein content of the experimental fish means that, they converted and utilized the protein from the feed into their body prtein. This result is similar with that of Marimuthu et al (2010) and Ali and Onder (2011). The findings were consistent with those of (Nubia et al, 2014) who found that, the protein content of wild catfish was 19.33±0.25%.…”
Section: Effect Of Experimental Diets On Initial and Final Muscles Co...supporting
confidence: 93%